(untitled) (Indian Journal of Arid Horticulture, 2025)
Bael (Aegle marmelos Correa) is one of the most utilitarian medicinal plants of India, it grows under adverse agro-climatic conditions. In the ancient medical Aurvedic treatise Charaka Samhita every part of this tree, stem, bark, root, leaves and fruits at all stage of maturity have medicinal merits and have been used as remedy for a long time. Alternaria alternate species is responsible for causing leaf spot disease in bael (Aegle marmelos). Symptoms initially started from leaf margin and tip of leaves which are irregular and light brown in colour, later converted into dark brown to grey. In severe condition several spots coalepsce to form large necrotic spots and covers large area.